Christianisme et politique en Amerique Latine: ou en est la Theologie de la Liberation? (Christianity and Politics in Latin America: where is the Theology of Liberation?) - DOI: 10.5752/P.2175-5841.2009v7n15p7 - Löwy, Michael (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2009)
Christianisme et politique en Amerique Latine: ou en est la Theologie de la Liberation? (Christianity and Politics in Latin America: where is the Theology of Liberation?) - DOI: 10.5752/P.2175-5841.2009v7n15p7